Detailed DoS attacks in wireless networks and countermeasures. (13th February 2007) - Mohammed, Lawan A.; Issac, Biju
IEEE 802.11 wireless networks have fuzzy boundaries, making it easy for an attacker to capture the transmitted packets. Also the attacker can send massive volume of illegitimate traffic and utilise system resources in a way that renders the system inoperable, thus denying access to authorised users. This paper is two fold in its description. Firstly, it describes some of the major vulnerabilities associated with wireless networks. Secondly, it demonstrates different methods of achieving Denial of Service (DoS) attacks in detail, as it applies to wireless networks and discusses and proposes different countermeasures to minimise the attacks.